Association of Cardiorespiratory Fitness Levels During Youth with Health Risk Later in Life: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (American Medical Association, 2020)
Importance: Although the associations between cardiorespiratory fitness (CRF) and health in adults are well understood, to date, no systematic review has quantitatively examined the association between CRF during youth and health parameters later in life. Objectives: To examine the prospective association between CRF in childhood and adolescence and future health status and to assess whether changes in CRF are associated with future health status at least 1 year later. Data Sources: For this systematic review and meta-analysis, MEDLINE, Embase, and SPORTDiscus electronic databases were searched for relevant articles published from database inception to January 30, 2020. Study Selection: The following inclusion criteria were used: CRF measured using a validated test and assessed at baseline and/or its change from baseline to the end of follow-up, healthy population with a mean age of 3 to 18 years at baseline, and prospective cohort design with a follow-up period of at least 1 year. Data Extraction and Synthesis: Data were processed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Random-effects models were used to estimate the pooled effect size. Main Outcomes and Measures: Anthropometric and adiposity measurements and cardiometabolic health parameters. Results: Fifty-five studies were included with a total of 37563 youths (46% female). Weak-moderate associations were found between CRF at baseline and body mass index (r =-0.11; 95% CI,-0.18 to-0.04; I2= 59.03), waist circumference (r =-0.29; 95% CI,-0.42 to-0.14; I2= 69.42), skinfold thickness (r =-0.34; 95% CI,-0.41 to-0.26; I2= 83.87), obesity (r =-0.15; 95% CI,-0.23 to-0.06; I2= 86.75), total cholesterol level (r =-0.12; 95% CI,-0.19 to-0.05; I2= 75.81), high-density lipoprotein cholesterol (HDL-C) level (r = 0.11; 95% CI, 0.05-0.18; I2= 69.06), total cholesterol to HDL-C ratio (r =-0.19; 95% CI,-0.26 to-0.13; I2= 67.07), triglyceride levels (r =-0.10; 95% CI,-0.18 to-0.02; I2= 73.43), homeostasis model assessment for insulin resistance (r =-0.12; 95% CI,-0.18 to-0.06; I2= 68.26), fasting insulin level (r =-0.07; 95% CI,-0.11 to-0.03; I2= 0), and cardiometabolic risk (r =-0.18; 95% CI,-0.29 to-0.07; I2= 90.61) at follow-up. Meta-regression analyses found that early associations in waist circumference (β = 0.014; 95% CI, 0.002-0.026), skinfold thickness (β = 0.006; 95% CI, 0.002-0.011), HDL-C level (β =-0.006; 95% CI,-0.011 to-0.001), triglyceride levels (β = 0.009; 95% CI, 0.004-0.014), and cardiometabolic risk (β = 0.007; 95% CI, 0.003-0.011) from baseline to follow-up dissipated over time. Weak-moderate associations were found between change in CRF and body mass index (r =-0.17; 95% CI,-0.24 to-0.11; I2= 39.65), skinfold thickness (r =-0.36; 95% CI,-0.58 to-0.09; I2= 96.84), obesity (r =-0.21; 95% CI,-0.35 to-0.06; I2= 91.08), HDL-C level (r = 0.05; 95% CI, 0.02-0.08; I2= 0), low-density lipoprotein cholesterol level (r =-0.06; 95% CI,-0.11 to-0.01; I2= 58.94), and cardiometabolic risk (r =-0.08; 95% CI,-0.15 to-0.02; I2= 69.53) later in life. Conclusions and Relevance: This study suggests that early intervention and prevention strategies that target youth CRF may be associated with maintaining health parameters in later life.. © 2020 American Medical Association. All rights reserved.